2014
DOI: 10.1039/c3ra47225f
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of excitation wavelength dependent photoluminescence in nano-CeO2 dispersed ferroelectric liquid crystals

Abstract: The optical properties of nano-ceria (nano-CeO 2 ) dispersed ferroelectric liquid crystals (FLCs) have been investigated by excitation wavelength dependent photoluminescence (PL) spectroscopy. The PL spectra of nano-ceria exhibited a strong excitation wavelength dependence in the 255-370 nm range. The red shift in the violet emission band of ceria i.e. from 368 nm to 396 nm with increasing excitation wavelength, has been attributed to the recombination of electrons trapped in the defect band and the deeply tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Based on this PL study, the emission bands lying between 365-400 nm for CeO 2 thin lms are ascribed to the charge transfer from Ce 4f to O 2p band due to different defect levels. 40,41 The weak bands at 400, 460 and 470 nm are found for N ion implanted lms. The observed band gap results are consistent with UV-vis spectroscopic results.…”
Section: Photoluminescence Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on this PL study, the emission bands lying between 365-400 nm for CeO 2 thin lms are ascribed to the charge transfer from Ce 4f to O 2p band due to different defect levels. 40,41 The weak bands at 400, 460 and 470 nm are found for N ion implanted lms. The observed band gap results are consistent with UV-vis spectroscopic results.…”
Section: Photoluminescence Studiesmentioning
confidence: 97%
“…It is suggested that the strong emission $369 nm for CeO 2 is attributed to the defects like dislocations or O defects supporting for prompt O mobility. 40,41 3.7 Magnetic measurements Fig. 9 shows the magnetization (M) vs. applied magnetic eld (H) dependence for P and N ion implanted CeO 2 thin lms.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…represent chiral smectic C, smectic A, chiral nematic, and isotropic phases, respectively. The effect of nanosized ceria particles on the optical textures of KCFLC has already been reported 14 and it was found that NPs are uniformly dispersed within the FLC and homogenous alignment could be retained up to 5 ml of ceria NPs dispersion. In order to identify the fundamental vibration of the functional groups present in the materials and to understand the structural deformation induced in the FLC matrix on dispersing CeO 2 NPs, IR spectroscopy has been used.…”
Section: Methodsmentioning
confidence: 92%
“…The optical properties of FLCs doped analogues with dopants like dispersion of nobel metal gold, silver, platinum of size $5 nm and palladium NPs, [13][14][15] barium titanate (BaTiO 3 ) NPs, 16 rare earth oxide nano-ceria 17 and ZnO/ZnS quantum dots 18 etc. have been studied by electro-optic and photoluminescence (PL) spectroscopy.…”
Section: -12mentioning
confidence: 99%
“…This UV emission peak corresponds to the radiative relaxation of electrons from the lowest unoccupied molecular orbital (LUMO) to the highest occupied molecular orbital (HOMO) energy levels in the FLC. 17 While, the visible emissions in 450-510 nm range exhibit continuous red shi with gradual fall in intensity on increasing excitation wavelength. The red shi in emission spectra can be understood in terms of columnar aggregates formation between the two structural components of FLC.…”
mentioning
confidence: 99%